A second Eocene species of death-watch beetle belonging to the genus Microbregma Seidlitz (Coleoptera: Bostrichoidea) with a checklist of fossil Ptinidae - Bukejs, Andris; Alekseev, Vitalii I. (Zootaxa, 2015)
Based on a well-preserved specimen from Upper Eocene Baltic amber (Kaliningrad region, Russia), Microbregma waldwico sp. nov., the second fossil species of this genus, is described. The new species is similar to the extant Holarctic M. emarginatum (Duftschmid), 1825, and fossil M. sucinoemarginatum (Kuśka), 1992, but differs in its shorter abdominal ventrite 1 (about 0.43 length of ventrite 2) and larger body (5.1 mm). A key to species of the genus Microbregma is given, and a check-list of described fossil Ptinidae is provided. The fossil record of Ptinidae now includes 48 species in 27 genera and 8 subfamilies.